Програма "Зварювальник" для дослідження впливу чинників виробничого середовища на здоров'я працюючого - Березуцький, Вячеслав Володимирович; Хондак, І. І. (Publishing office RS Global Media LLC company, 2020)
In today's world, gamification is widely used as one of the most effective approaches to learning. Developed and implemented in the educational process work "Welder" is a visual tool in the study of the influence of factors of the production environment and the work process on the health of the working and environment in the welding process. The use of such works in various forms of training is very important and necessary in modern conditions. This is especially true for distance learning. With distance learning, where there is virtually no "live" communication with the teacher, there are difficulties in presenting theoretical material. In connection with this, a new computer simulation program was developed and introduced into the educational process at the Department of Occupational Safety at Kharkiv National University of Radio Electronics. The program, which gives an opportunity to clearly visualize the impact of various factors on the welder and the environment, introduces methods and means of protection against their negative impact.
Keywords: програма "Зварювальник"; виробниче середовище; здоров'я; засоби захисту людини; influence; factor; gamification; distance learning; computer games; welding